环境伦理学的种类 - Rolston, Holmes, 1932-2025, author; Taiwan Ecological Stewardship Association, publisher (Colorado State University. Libraries, 2007)
Twelve types of environmental ethics: 1. Humanistic and naturalistic ethics. 2. A triangular affair: humans, animals, and a land ethic. 3. Biocentrism and respect for life. 4. Deep ecology. 5. Theology and the environment. 6. Expanding communities, concentric circles. 7. Axiological environmental ethics: intrinsic, instrumental, and ecosystemic values. 8. Political ecology and green politics. 9. Sustainable development and sustainable biosphere. 10. Bioregionalism. 11. Ecofeminism. 12. Pluralism, postmodernism, and a sense of place. Variously constructed kinds of environmental ethics need to join as all humans see themselves as Earthlings, with their home planet as a responsibility.
Ethics and the environment
Text in Chinese.
Keywords: naturalistic ethics; humanistic ethics; bioregionalism; biocentrism; sustainable development; environmental ethics